Effect of the Phosphorus Gettering on Si Heterojunction Solar Cells. (22nd February 2012) - Park, Hyomin; Tark, Sung Ju; Kim, Chan Seok; Park, Sungeun; Kim, Young Do; Son, Chang-Sik; Lee, Jeong Chul; Kim, Donghwan
Abstract : To improve the efficiency of crystalline silicon solar cells, should be collected the excess carrier as much as possible. Therefore, minimizing the recombination both at the bulk and surface regions is important. Impurities make recombination sites and they are the major reason for recombination. Phosphorus (P) gettering was introduced to reduce metal impurities in the bulk region of Si wafers and then to improve the efficiency of Si heterojunction solar cells fabricated on the wafers. Resistivity of wafers was measured by a four-point probe method. Fill factor of solar cells was measured by a solar simulator. Saturation current and ideality factor were calculated from a dark current density-voltage graph. External quantum efficiency was analyzed to assess the effect of P gettering on the performance of solar cells. Minority bulk lifetime measured by microwave photoconductance decay increases from 368.3 to 660.8 μ s. Open-circuit voltage and short-circuit current density increase from 577 to 598 mV and 27.8 to 29.8 mA/cm 2, respectively. The efficiency of solar cells increases from 11.9 to 13.4%. P gettering will be feasible to improve the efficiency of Si heterojunction solar cells fabricated on P-doped Si wafers.